Analysis of Building Electrical Lighting System Tomohon City Regional Drink Water Company - Walandouw, Frederico; Seke, Fransiskus; Rapar, Jocke (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
This study aims to see whether the electrical lighting installation at the Regional Drinking Water Company (Indonesian, abbreviated as PDAM) of Tomohon City follows the General Requirements for Electrical Installations (abbreviated as PUIL) or vice versa. Using the analysis approach, direct observation was performed at the research site, and after performing the study, it was discovered that many electrical lighting installation requirements did not satisfy PUIL. Following the measurements and calculations, it was found that none of the lighting in building A met PUIL standards, while for building B, there was only 1 room whose lighting met PUIL standards. Furthermore, there were several rooms where the lights were not installed. Of course, this can affect the daily activities in the room. From the results of the study, it is inevitable that the electrical lighting installation in the PDAM building in Tomohon City must be repaired immediately and should follow the applicable PUIL.